PEMANFAATAN COPPER SLAG SEBAGAI SUBSTITUSI PASIR PADA CAMPURAN BETON MUTU K-225 - muhammad syahrizal mauludi (Jurnal Teknik Sipil dan Lingkungan, 2014)
Utilization of industrial soil waste or secondary materials has encouraged in construction field for the production of concrete because it contribute to reducing the consumption of natural resources. Copper slag is one of the materials that is considered as a waste from PT. Smelting Gresik Company which could have a promising future in construction Industry as partial aggregates. Many researchers have already found it possible to use copper slag as a concrete aggregate. But not much research has been carried out in Indonesia concerning as a replacement for sand in concrete mixes. This paper presents the results of an experimental study on copper slag as a replacement for sand in concrete mixes for fc'18,675 MPa in Cylinder 15 cm x 30 cm by SNI 03-2834-2000 Standard. The effect of replacing fine aggregate by copper slag on the compressive strength is attempted in this work. The percentage replacement of sand by granulated copper slag were 0%, 10%, 20%,3 0% and 35%. The compressive strength was observed to increase by about 10-35% from normal concrete. The experimental investigation showed that percentage replacement of sand by copper slag shall be up to 30%. Keywords : Copper Slag, Compressive Strenght,Â  Partial Replacement of Sand, Concrete